The convergence clubs of Regional Comprehensive Economic Partnership (RCEP) countries: a wise choice? - Dayang Affizah Awang Marikan,; Md.Mahbubur Rahman,; Nor Afiza Abu Bakar,; Ting, Mee Sing (Penerbit Universiti Kebangsaan Malaysia, 2017)
This investigation used the non-linear approach on the income convergence issues of the Regional Comprehensive Economic Partnership (RCEP) countries to evaluate empirically the income convergence during the period 1997-2015. Alternatively, if two or more nations have shown to some degree of income convergence, it can be useful to identify the uniformity of economic performance. Because of the excessive output inequalities between members and between regions, a full aggregate convergence failed to be established yet the study further facilitates the endogenous decision of clubs convergence (sub groups). Evidence from income convergence indicates that a group of developed nations, particularly Singapore, Japan, New Zealand and Brunei comprised of the core clubs, Malaysia, China, Thailand and Indonesia, known as newly industrialized economies (NIES’s) clustered into a group. Finally, the remaining countries, converging towards each other forming another club. Seven clubs convergence implies that the RCEP members experience weak convergence between them which illustrate relatively substantial dissimilarity in its structure of the economy as a whole. Despite the dissimilarity, the speed of convergence indicates that possible catching up within the members countries, in converging towards a similar transition path of economics growth. Thus indicating further realisation of economic corporation and stronger integration among the RCEP members now and in the future.